ANALISIS PENERIMAAN PENGGUNA PRODUK E-MONEY GOPAY TERHADAP MINAT MENGGUNAKAN GO-PAY DI BANDAR LAMPUNG - Ismail, Taufik; Sugiono, Arif; Subagja, Ghia (Jurnal Kompetitif Bisnis, 2023)
As an effort to realize the goal of Indonesia's cashless national movement, it is to support and develop electronic money as a non-cash payment instrument. One of the non-cash payment instruments is e-Money Go-Pay. This study aims to analyze the user acceptance of e-Money products on the intention to use Go-Pay in Bandar Lampung. The variables analyzed are based on the TAM (Technology Acceptenance Model) theory, including perceptions of usefulness and perceived ease of use, as well as other supporting variables, namely security perceptions that affect intention to use Go-Pay e-Money services. This type of research is explanatory with a quantitative approach. The sampling technique used incidental sampling with a sample of 100 respondents. Data analysis in this study used multiple linear regression analysis. The results of the study explain that, partially, the perception of usefulness, the perception ease of use, and the perception of security have a significant effect on the intention to use Go-Pay in Bandar Lampung. Simultaneous test results show that perceived usefulness, perceived ease of use, and perceived security have an effect on intention to use Go-Pay in Bandar Lampung.